What is a Non-Performing Loans (NPLs) from the Malaysian perspective? / Dr. Mohamad Hanif Abu Hassan, Dr. Muhammad Zarunnaim Wahab and Wahidah Shari - Abu Hassan, Mohamad Hanif; Wahab, Muhammad Zarunnaim; Shari, Wahidah (Universiti Teknologi MARA, Kedah, 2023)
A non-performing loan (NPL) is one for which the borrower has failed to make scheduled payments for a specified period. The exact definition of "non-performing" depends on the terms of the loan, but "no payment" usually means that neither the principal nor the interest has been paid.